Impact of feeding strategies on the growth and nutrient discharge in the polyculture of carps using farm ponds - Sharma, Pawan Kumar; Sampath Kumar, John Stephen; MANIKANDAVELU , D (The Indian Journal of Animal Sciences, 2022)
The present study aimed at evaluating appropriate feeding strategies to obtain maximum fish production from farm ponds at low/minimum investment costs was carried out under the Tamil Nadu-Irrigated Agriculture Modernization Project financed by the World Bank. The study was carried out for 180 days at the Directorate of Sustainable Aquaculture, Thanjavur, in four, equal-sized, farm ponds with two treatments in duplicates by stocking5 species (Catla catla, Labeo rohita, Cirrhinus mrigala, Ctenopharyngodon idella and Cyprinus carpio) in theratio of 1:1:1:1:2. Treatment 1 (T1) involved the feeding strategy of pelleted feed with 20% CP (crude protein)broadcast twice a day whereas in Treatment 2 (T2), the same feed was provided four times a day as feed ballsusing feed trays. Among the five species, C. carpio (779±189.01 g) and C. mrigala (670±121.38 g) stocked inT2 attained the maximum weight. Production parameters such as gross production, net production, average dailygrowth rate were not significant between the treatments, however T2 showed comparatively better results than T1.Survival rate of fishes was recorded significantly higher in T1 (35.54±2.60%) than in T2 (29.6±2.36%). Nutrientssuch as total phosphorus, total nitrogen and total potassium were significant and highly discharged in T1 than inT2. Experiment revealed that feeding fishes in trays helped to monitor the weight gain and feed intake with reducednutrient discharge, thereby proper feed management was obtained in T2 when compared to T1